Incidental Urinary Bladder Leiomyoma: A Successful Long Term Conservative Treatment Based on Pre-operatory Magnetic Resonance Imaging Findings. Issue 4 (23rd November 2018) - Prayer-Galetti, Tommaso; Scagliori, Elena; Stramare, Roberto; Tregnaghi, Alberto; Moro, Fabrizio Dal; Zattoni, Fabio; Gardiman, Marina Paola; Soligo, Matteo
No abstract available